2015
DOI: 10.1128/jcm.02818-14
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Virulent Newcastle Disease Virus in Vaccinated Chickens in Farms in Pakistan

Abstract: One year after a virulent Newcastle disease virus (vNDV) outbreak in Pakistan, the causative strain was present in vaccinated chickens of multiple farms despite the existence of high-average NDV-specific antibody titers (>4.75 log 2 ). The data suggest a possible role of vaccinated birds as reservoirs of vNDV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 9 publications
3
47
0
1
Order By: Relevance
“…The sequence data described here provide evidence that vNDV strains were circulating among vaccinated flocks in three different provinces of Indonesia during 2013 to 2014. Vaccination can prevent or reduce clinical disease, but NDV can still circulate in vaccinated flocks (15)(16)(17), as also demonstrated here. Thеsе facts highlight the need for continuous vaccine evaluation and development of improved vaccines for disease control (18,19).…”
supporting
confidence: 72%
“…The sequence data described here provide evidence that vNDV strains were circulating among vaccinated flocks in three different provinces of Indonesia during 2013 to 2014. Vaccination can prevent or reduce clinical disease, but NDV can still circulate in vaccinated flocks (15)(16)(17), as also demonstrated here. Thеsе facts highlight the need for continuous vaccine evaluation and development of improved vaccines for disease control (18,19).…”
supporting
confidence: 72%
“…Even though birds vaccinated with inactivated vaccines tend to have higher humoral antibody levels, they do not develop a strong cell mediated response (Schijns et al, 2013), and shed larger amounts of virulent challenge virus compared to birds vaccinated with live ND vaccines (Miller et al, , 2009. Although live and inactivated vaccines protect against clinical disease in SPF chickens, there are continuous reports of vaccine failures under field conditions (Perozo et al, 2012;Rehmani et al, 2015). One of the possible reasons for these failures may be poor vaccination response that is also dependent on field-associated factors unrelated to the vaccines, such as immunosuppression (Meulemans, 1988) from infections prior to ND vaccination.…”
Section: Traditional Vaccinesmentioning
confidence: 99%
“…Currently, ND is still a serious threat to the poultry industry, even though intensive vaccination programs have been applied. Recently, some studies have reported ND outbreaks among vaccinated commercial flocks, causing up to 76.8-84.4% mortality in India [19], 70-80% mortality in Indonesia [45], 60-70% mortality in Japan [40], and 5-50% mortality in Pakistan [29]. In Egypt, ND was first reported in 1948 [6], and it was classified as an endemic disease by the beginning of the 1960s [10].…”
Section: Discussionmentioning
confidence: 99%